Organized crime on the UN Security Council agenda: action against human trafficking reveals opportunities and challenges - Vorrath, Judith (SWP comment)
On 7 June 2018, for the first time, a Committee of the United Nations Security Council placed individuals on a sanctions list for human trafficking. As part of the Libya sanctions regime, travel bans and asset freezes have been imposed on six individuals identified as the main perpetrators of illegal activities relating to human trafficking and the smuggling of migrants. The European Union and the US have already implemented these UN sanctions. This response is an expression of the UN Security Council’s increased attention on transnational organized crime (TOC). For years, the number of resolutions relating to TOC, whether linked to drug or arms trafficking, piracy, kidnappings or illegal trade in natural resources, has increased substantially. And the Security Council has repeatedly dealt with human trafficking in conflict situations since the end of 2015. The relevant decisions show what role the Security Council can play in addressing organized crime, but also where pitfalls lurk. As a non-permanent member of the Security Council in 2019/2020, Germany should advocate a systematic advancement of the agenda.